Re-Considering Contemporary State Criminality: A Theoretical Framework of State Crimes Against Democracy (SCADS) - Uibariu, Alexandra M. (Kriminalističke teme, 2018)
With an acknowledgement that state criminality extends beyond the actions of authoritarian regimes in feeble political systems, this paper calls for a re-consideration of political deviance under an inter-disciplinary framework which allows for a theorisation of State Crimes Against Democracy (SCADs). Formulated on the basis of the academic thought stemming from public administration, political science and criminology, the definition and (budding) theory of SCADs lays the case for a review of the critical criminological agenda to consider the harmful (and often criminal) actions and inactions of democratic governments in their efforts to undermine popular sovereignty. SCADs are constructed as crimes of omission or commission which encompass electoral manipulation and incapacitation, political unaccountability, and breaches of human, civil and political rights, and which often result in the destabilisation of the rule of law and economic development, the undermining of broader social norms, moral values and public trust in democratic institutions, and the promotion of various other types of criminality.